Developing and investigating a pure Monte-Carlo module for transient neutron transport analysis. (June 2017) - Mylonakis, Antonios G.; Varvayanni, M.; Grigoriadis, D.G.E.; Catsaros, N.
Highlights: Development and investigation of a Monte-Carlo module for transient neutronic analysis. A transient module developed on the open-source Monte-Carlo static code OpenMC. Treatment of delayed neutrons is inserted. Simulation of precursors' decay process is performed. Transient analysis of simplified test-cases. Abstract: In the field of computational reactor physics, Monte-Carlo methodology is extensively used in the analysis of static problems while the transient behavior of the reactor core is mostly analyzed using deterministic algorithms. However, deterministic algorithms make use of various approximations mainly in the geometric and energetic domain that may induce inaccuracy. Therefore, Monte-Carlo methodology which generally does not require significant approximations seems to be an attractive candidate tool for the analysis of transient phenomena. One of the most important constraints towards this direction is the significant computational cost; however since nowadays the available computational resources are continuously increasing, the potential use of the Monte-Carlo methodology in the field of reactor core transient analysis seems feasible. So far, very few attempts to employ Monte-Carlo methodology to transient analysis have been reported. Even more, most of those few attempts make use of several approximations, showing the existence of an "open" research field of great interest. It is obvious that comparing to static Monte-Carlo, a straight-forward physical treatment of a transient problem requires the temporal evolution of the simulated neutrons; but this is not adequate. In order to be able to properly analyze transient reactor core phenomena, the proper simulation of delayed neutrons together with other essential extensions and modifications is necessary. This work is actually the first step towards the development of a tool that could serve as a platform for research and development on this interesting but also quite challenging field. More specifically, in this work, a capability for transient neutronic analysis has been introduced in the open-source Monte Carlo code OpenMC. The selected methodology that has been proposed recently by other researchers is inserted in OpenMC following its own features, trying to minimize the necessary modifications and to maximize the advantage by its existing capabilities. The key points of the module which is under development, as well as the results of the analysis of preliminary numerical experiments are presented and discussed. The obtained results are encouraging and very promising in terms of accuracy, giving motivation for further investigation and development.